Hepatic apoptotic markers are not predictors for the virological response to interferon-based therapy in chronic hepatitis C patients - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
IntroductionChronic hepatitis C virus (HCV) infection is a major health problem worldwide. The majority of cases involving HCV infection develop into chronic hepatitis because of a failure to develop an effective immune response. Apoptosis of the hepatocytes plays a significant role in the pathogenesis of HCV infection: the interaction between the Fas antigen on hepatocytes and the Fas ligand on T cells corresponds to the main mechanism for hepatocyte damage. Interferon (IFN)- has antiviral, immunoregulatory, and antiproliferative properties, and apoptosis seems to be a critical event in the action mechanisms of both IFNs. In this study, we aimed to detect any relationship between apoptotic markers in the liver and the response to the treatment.Materials and methodsThe study included 180 chronic HCV patients treated with IFN and ribavirin in four centers. Apoptotic markers (Fas, Fas ligand, Fas-associated death domain, caspases 3, 8, and 9, and in-situ apoptosis) were studied in the liver. The age, sex of the patients, response to therapy, ALT level, viral load, and genotype were recorded.ResultsThe results of the study showed that the histological activity index and fibrosis correlated with CD95 staining density, caspase-8 intensiveness, and portal and parenchymal Fas ligand scores. The apoptotic parameters of the responsive cases were not significantly different from those of the unresponsive cases.ConclusionThe apoptotic parameters studied in liver tissue are associated with inflammation and fibrosis; however, these parameters may not predict response to treatment.
Keywords: apoptosis; chronic hepatitis C; inflammation; interferon; FAS-MEDIATED APOPTOSIS; HEPATOCYTE APOPTOSIS; EXPRESSION; LIVER; ANTIGEN; LIGAND; CELLS; BCL-2; STEATOHEPATITIS; PROLIFERATION